Improvement of Urodynamic Indices by Single Dose Oral Tadalafil in Men With Supra Sacral Spinal Cord Injury - Taie, Karim; Moombeini, Hayat; Khazaeli, Dinyar; Salari Panah firouzabadi, Mohammad (Urology Journal, 2010)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE FA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:Arial; mso-bidi-theme-font:minor-bidi;} --> <!--[endif]--> Purpose: To investigate the changes in urodynamic indices following a single dose of oral tadalafil in patients with supra sacral spinal cord injury (SCI). Materials and Methods: Urodynamic study was accomplished on 20 patients with supra sacral SCI before and one hour after administration of 20 mg oral tadalafil as a single dose. Changes in the bladder capacity and compliance, maximum voiding detrusor pressure, and maximum detrusor filling pressure before and after tadalafil administration were recorded. Results: Following administration of 20 mg oral tadalafil, there was a significant increase in the bladder compliance (from 12.7 to 18.5 mL/cmH20, P < .001), bladder capacity (from 169.8 to 198.5 mL, P < .001), maximum voiding detrusor pressure (from 64.8 to 48.6 cmH2O, P < .001), and maximum detrusor filling pressure (from 24.3 to 14.0 cmH2O, P < .001). Conclusion: Single dose of oral tadalafil has significant positive effects on urodynamic indices in patients with supra sacral SCI.